DNA Damage-Induced RNAPII Degradation and Its Consequences in Gene Expression - Muñoz, Juan Cristóbal (2022)
RPB1, the major and catalytic subunit of human RNA Polymerase II (RNAPII), is specifically degraded by the ubiquitin–proteasome system upon induction of DNA damage by different agents, such as ultraviolet (UV) light. The “last resort” model of RNAPII degradation states that a persistently stalled RNAPII is degraded at the site of the DNA lesion in order to facilitate access to Nucleotide Excision Repair (NER) factors, thereby promoting repair in template strands of active genes. Recent identification and mutation of the lysine residue involved in RPB1 ubiquitylation and degradation unveiled the relevance of RNAPII levels in the control of gene expression. Inhibition of RNAPII degradation after UV light exposure enhanced RNAPII loading onto chromatin, demonstrating that the mere concentration of RNAPII shapes the gene expression response. In this review, we discuss the role of RNAPII ubiquitylation in NER-dependent repair, recent advances in RPB1 degradation mechanisms and its consequences in gene expression under stress, both in normal and repair deficient cells.